Análisis comparativo de los costos de producción del litro de leche en dos razas de bovinos Holstein Americana y Holstein Neozelandesa en similares sistemas de producción, en la hacienda Bretaña, cantón Cayambe, provincia de Pichincha - Jibaja Alvear, Camilo Vicente (2015)
The research called "Comparative Analysis of Production Costs per liter of milk in two breeds of cattle and American Holstein Holstein in New Zealand Related Production Systems at Hacienda Britain, Canton Cayambe, Pichincha Province" aimed to: determine the profitability of the production of cow's milk in two dairy breeds, estimate the productive efficiency of each breed and disseminate the results to the farmers in the area are aware of the benefits of the best producer race. The methodology consisted of a brief analysis of the organizational structure of the farm, where the necessary data for identification records of animals found in milk production were collected; They made a separation between the production line with the race belonging cows, whether they are American or New Zealand holstein; reproductive log, grazing, logging existence of cattle, animal health record, record revenues and expenditures; that allowed us to evaluate the following variables: Wages and salaries, utilities, furniture and fixtures, toilet utensils, equipment and tools, the estimation of ground rent, own machinery, forage feed, food lavished by balanced, vaccinations, worming, inseminations, antibiotics, gynecological treatments, to get to the heart of this research work, the comparative analysis of the production cost of a liter of milk in two breeds of dairy cattle. The results show that the selling price of raw milk on the farm is forty-four cents a liter regardless of race to which he belongs, the production cost for a liter of milk regardless of race to which it belongs It is thirty-seven cents, the average yield for a cow of American Holstein is eleven point eighty-five liters of milk, the average yield of a cow of New Zealand Holstein breed is thirteen point ninety seven liters, the difference in average individual output is two point twelve liters per capita in favor of New Zealand Holstein. In conclusion it can be observed that the New Zealand Holstein is more profitable because it produces more milk, eat less grass, its hardiness has needed less spending on medicines. the farmers in the area hybridizations We recommend starting with New Zealand Semen for smaller capital investment and profit.